Free Competition in Rail Transport: A Liberal Approach of the Shortlines’ Proposal - Lanza, João Felipe Rodrigues (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2020)
With the truckers’ strike of 2018, it became evident the need to increase the use of the railway modal in Brazil, currently insufficient for the needs of the country and turned almost completely to the transportation of commodities. A liberal proposal is to reuse the several stretches currently idle along the railway network on the lines of the north American shortlines. To this objective, an introduction of competition should be sought in the light of the Austrian theory of markets as processes, in contrast of the mainstream analysis of natural monopoly structures. The present article aims to analyse the necessary reforms through a literature review of the Brazilian and North American experiences.